Potassium-sensitive loss of muscle force in the setting of reduced inward rectifier K + current: Implications for Andersen–Tawil syndrome - Nathaniel Elia; Marbella Quiñonez; Fenfen Wu; Ekaterina Mokhonova; Marino DiFranco; Melissa J. Spencer; Stephen C. Cannon (Proceedings of the National Academy of Sciences, 2025)
Andersen–Tawil syndrome (ATS) is an ion channelopathy with variable penetrance for the triad of periodic paralysis, arrhythmia, and dysmorphia. Dominant-negative mutations of KCNJ2 encoding the Kir2.1 potassium channel subunit are found in 60% of ATS families. As with most channelopathies, episodic attacks in ATS are frequently triggered by environmental stresses: exercise for periodic paralysis or stress with adrenergic stimulation for arrhythmia. Fluctuations in K + , either low or high, are potent triggers for attacks of weakness in other variants of periodic paralysis (hypokalemic periodic paralysis or hyperkalemic periodic paralysis). For ATS, the [K + ] dependence is less clear; with reports describing weakness in high-K + or low-K + . Patient trials with controlled K + challenges are not possible, due to arrhythmias. We have developed two mouse models (genetic and pharmacologic) with reduced Kir currents, to address the question of K + -sensitive loss of force. These animal models and computational simulations both show K + -dependent weakness occurs only when Kir current is <30% of wildtype. As the Kir deficit becomes more severe, the phenotype shifts from high-K + -induced weakness to a combination where either high-K + or low-K + triggers weakness. A K + channel agonist, retigabine, protects muscle from K + -sensitive weakness in our mouse models of the skeletal muscle involvement in ATS.